The relationship between ultrasonography with or without contrast and the clinical outcome in plantar fasciitis. (9th August 2022) - Johannsen, Finn; Magnusson, Stig Peter
Abstract : Background: Plantar fasciitis (PF) is a common disorder without objective parameters for disease severity. Purpose: To investigate whether structural changes in the plantar fascia and heel fat pad determined by ultrasound scanning with or without contrast are related to outcome measures in patients with symptomatic PF and to investigate whether there is an association between changes in US findings and improvement in pain and function. Methods: All patients ( n  = 90) in a randomized controlled trial treated with training and/or glucocorticosteroid injection were assessed for morning pain, function pain, Foot Function Index (FFI), and ultrasound measured thickness of the fascia and heel fat pad at entry and after 6 months. Thirty patients were included in a longitudinal study that assessed pain, function, and microvascular volume (MV) by contrast‐enhanced ultrasound at entry and after 5 months of treatment. Results: None of the ultrasound parameters at the initial examination were related to clinical outcomes at 5–6 months. Changes in US measured thickness of the fascia but not the fat pad correlated with improvement in all outcome measures at 6 months (FFI: r  = 0.30, p  = 0.005, morning pain: r  = 0.21, p  = 0.046, function pain: r  = 0.28, p  = 0.007). MV did not change despite significant improvement in symptoms. Conclusion: Changes in ultrasound measured fascia thickness are associated with clinical improvement in PF patients.